THE IMPACT OF RECREATIONAL PHYSICAL ACTIVITY ON HEALTH AND WELL-BEING OF OLDER ADULTS - Iris MALKA; Iacob HANTIU (Editura Universităţii din Oradea, 2022)
Recent studies showed that recreational physical activity has positive affect on people's health and well-being. This research study aimed to investigate the effect of two different types of recreational physical activity, the Fitness and the Harmonic Gymnastics, on health and well-being of older adults. Thirty-nine healthy adults aged 50 years and older from Tel-Aviv, volunteered to participate in this research program, and were divided into three groups: 7 subjects who did not participate in any physical activity program, 16 subjects in the Fitness and 16 in the Harmonic Gymnastics intervention programs. They filled a consent form and answered the SF-36 questionnaire. The data was analyzed though the SPSS v. 23.0 statistical program. The results showed that the No PA group decreased all health and well-being subscales, except the emotional well-being, which revealed no differences. The two active groups improved several health and well-being subscales and significantly improved the health and well-being composite score (p = 0.015, d = 0.35 in the Fitness and p = 0.001, d = 0.5 in the HG). The differences between the groups occurred mainly in the emotional well-being subscales. The Fitness group improved some of the emotional well-being subscales but decreased the social well-being, while the HG group did not reveal significant differences in the emotional or social well-being. This study highlighted the benefits of recreational physical activity on the health and wellbeing of older adults, and also the negative effects of sedentary behavior. It would be necessary to investigate the two types of recreational physical activity in normal conditions, rather than in Covid-19 period of time.